Bismuth breast-shield use in chest computed tomography for efficient dose reduction and sufficient image quality. Issue 25 (25th June 2021) - Ko, Chih-Hsiang; Lee, Shiou-Ping; Hsieh, Yi-Chien; Lee, Yuan-Hao; Yao, Melissa Min-Szu; Chan, Wing P.
Abstract: Background: Radiosensitivity in the breasts increases the risk of carcinogenesis from exposure to the ionizing radiation of computed tomography (CT) administered in the course of medical attention. Bismuth shielding techniques have been used to reduce radiation, but image noise increased, degrading image quality. Purpose: The aim of this study was to investigate how the use of iterative reconstruction (IR) combined with bismuth shielding influences image quality. Materials and Methods: Women aged at least 20 years with body mass indexes <28 were recruited and randomly assigned to 1 of 3 CT scanning protocols without shielding, with a bismuth breast shield before the scout view, or with a bismuth breast shield after the scout view. All obtained images were reconstructed using an IR algorithm. To evaluate radiation dose, 2 Gafchromic films were placed over the clothes, 1 near each nipple. Results: Average dose reduction was significant (27.99%, P  < .05) when bismuth shielding was applied after the scout view. Using the contrast-to-noise ratio, the image quality was found to be superior when the IR algorithm was applied. Using quantitative evaluations by 2 radiologists applying a 4-point Likert scale, significant differences in image quality were not found among the 3 protocols. Conclusion: Bismuth breast shields, particularly when used after acquiring scout images, are effective at reducing radiation dose without undermining the diagnostic value of the images when the IR technique is applied.